2023
DOI: 10.3390/ijerph20043714
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Ponseti Method in the Treatment of Clubfoot: A Systematic Review

Abstract: Clubfoot is a common congenital deformity of the lower limbs. It should be treated as soon as possible so that its correction is more easily achieved. The objective of this systematic review was to assess the effectiveness of the Ponseti method in the treatment of clubfoot. A bibliographic search was carried out in different databases, including PubMed and SciELO. Filters such as full text and randomized controlled trial were selected to find those articles that best matched our search. Among the results, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The success rates and relapse rates were noted to vary greatly between studies, and this may be attributed to various additional factors. It was demonstrated that the success of the Ponseti method depends on age, gender, and early diagnosis [1]. Conservative treatment in the first weeks of life has been recommended for clubfoot [3,8,11,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The success rates and relapse rates were noted to vary greatly between studies, and this may be attributed to various additional factors. It was demonstrated that the success of the Ponseti method depends on age, gender, and early diagnosis [1]. Conservative treatment in the first weeks of life has been recommended for clubfoot [3,8,11,27].…”
Section: Discussionmentioning
confidence: 99%
“…Clubfoot is a congenital deformity of the lower extremities [1]. This condition affects the musculoskeletal structures of the foot, including the equinus, varus, cavus, and adducts [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biomechanics of the Ponseti method have been studied extensively, and research has shown that this approach is highly effective, with up to 95% success rates. Related studies have also shown that the Ponseti method leads to better long-term outcomes and fewer complications than traditional surgical approaches [ 8 , 9 , 10 ]. Recently, nearly all orthopedics have agreed that conservative treatment is the best choice to correct CF [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It proved to be a valuable clinical tool, without including elements of local functional status, radiological picures or walking status. The Ponseti method is the standard conservative treatment for patients with TEV, initially designed by Prof. Ignacvio Ponseti in Iowa and then adopted in many pediatric orthopedic centers (7)(8)(9)(10). It is recommended to start the Ponseti tratment as soon as possibly after birth in childen with TEV.…”
mentioning
confidence: 99%